Genetic Factors in Systemic Lupus Erythematosus: Contribution to Disease Phenotype - Fulvia Ceccarelli; Carlo Perricone; Paola Borgiani; Cinzia Ciccacci; Sara Rufini; Enrica Cipriano; Cristiano Alessandri; Francesca Romana Spinelli; Antonio Sili Scavalli; Giuseppe Novelli; Guido Valesini; Fabrizio Conti (Journal of Immunology Research)
Genetic factors exert an important role in determining Systemic Lupus Erythematosus (SLE) susceptibility, interplaying with environmental factors. Several genetic studies in various SLE populations have identified numerous susceptibility loci. From a clinical point of view, SLE is characterized by a great heterogeneity in terms of clinical and laboratory manifestations. As widely demonstrated, specific laboratory features are associated with clinical disease subset, with different severity degree. Similarly, in the last years, an association between specific phenotypes and genetic variants has been identified, allowing the possibility to elucidate different mechanisms and pathways accountable for disease manifestations. However, except for Lupus Nephritis (LN), no studies have been designed to identify the genetic variants associated with the development of different phenotypes. In this review, we will report data currently known about this specific association.